Analisis Yuridis Pengesahan Perkawinan Beda Agama Dalam Putusan Nomor 916/PDT.P/2022/PN.SBY - Detto Kharisma Rovanno; Aris Munandar; Diangsa Wagian (Fakultas Hukum Universitas Mataram, 2023)
Indonesian society has diversity in terms of religious beliefs. an inter religious marriage in unavoidable. National law level law on marriage is Law on Marriage, but the law does not accommodate and recognize inter religious marriage thus according to the law. Currently, Surabaya District Court in their verdict granted the request of inter religious marriage in which according to the Indonesian legal sources, jurisprudence is one of the recognized legal sources. Therefore, aims of this study were to analyse Surabaya District Court’s verdict, and also to examine the legal standing of inter religious marriage in the Law on Marriage. This research was normative legal study, which used conceptual, statute and case approaches. The results have shown that inter religious marriage has juridical legality to be registered by Civil Registration Body through court ruling according to the provisions of Art 21 Marriage Law and Art 35 letter a Law on People Administration.